Aplicación móvil para promoción de la salud oral - Paúl Anderson, Berrones Montero (2021)
ABSTRACT Mobile applications are currently digital tools used by many people worldwide. Many of these Apps are focused on the field of health and education. This research aimed to design a mobile application for the Android operating system focused on promoting oral health in children through interactive activities based on the Oral Health Education Guide. For this purpose, a descriptive, observational, cross-sectional cohort study with a mixed approach was carried out. A survey was used as a data collection technique and a satisfaction and usability questionnaire as an instrument. The study population consisted of 168 participants from which a non-probabilistic intentional sample was taken by convenience based on the research purposes, selecting 120 girls and boys, who were employing informed consent agreed to participate in the project using the mobile application designed. The results were processed in the statistical program SPSS v.25. Usability between high and medium of approximately 79% and a low level of only 21% was found. Similarly, participants showed satisfaction with the application at a medium and high level with a percentage of 83%, with a low level of only 17%. This shows that implementing a mobile application in oral health promotion has a strong influence on user satisfaction and can be used for didactic purposes to teach children better. Key words: Mobile application, oral health promotion, health education. Reviewed by: Dr. Narcisa Fuertes, PhD. ENGLISH PROFESSOR cc: 1002091161